Micromachined tunable filters using MEMS switches and electromagnetic bandgap structures - Muhammad Faeyz Karim (2010)
Wireless communication is showing an explosive growth of emerging consumer military applications of radio frequency (RF), microwave, and millimeter-wave circuits and systems. Future handheld devices, ground comunications systems as well as communications satellites necessitate the use of highly integrated and reconfigurable RF front-ends, featuring small size, low weight, high performance and low cost. Continuing chip scaling has contributed to the extent that chip-off bulky passive RF coponents, like high-Q inductors, ceramics and SAW filters, varactors diodes and discrete PIN diode switches applications have become limiting. micro-machining or microelectromechanical systems (MEMS) technology is now rapidly emerging as an enabling technology to yield a new generation of high-performance RF-MEMS devies to replace these off-chip passives components in wireless comunication sub-systems.